Écrire quand le voyage vous défait : La relation viatique entre reliance et résilience - Gilles Louÿs (Viatica)
Many travels end badly: Nicolas Bouvier reported in Le Poisson-Scorpion his terrible stay in the island of Ceylon (now called Sri Lanka) in 1955. Michel Vieuchange died at the end of his 1930 hike through the Moroccan desert, and twenty years later Raymond Maufrais knew the same fate in the Guyana jungle. Whereas these two only left behind daily logs of their travels, Nicolas Bouvier elaborated a fully literary work from his Ceylonese shipwreck. Despite their differences, these three documents introduce the issue of how one can report a traumatic experience. This paper analyses the value of writing in the light of the concepts of “reliance” and “resilience”.